A new and threatened island-dwelling species of Cycloramphus (Anura : Cycloramphidae) from southeastern Brazil - Brasileiro, Cinthia A.; Haddad, Celio F. B. [UNESP]; Sawaya, Riccardo J.; Sazima, Ivan (Herpetologists League, 2007)
We describe a new species of Cycloramphus of the eleutherodactylus group from the Ilha dos Alcatrazes, southeastern Brazil, with descriptions of advertisement and territorial calls and notes on natural history. Additionally, we describe the advertisement and territorial calls of C. eleutherodactylus. The new species is diagnosed by the following set of characters: snout truncate in lateral and dorsal views; head wider than long; eyes protruding; tibia shorter than thigh; and distinct advertisement call. The new species is known from a single population on the Ilha dos Alcatrazes, a 149 ha island about 35 kin off São Paulo State coast where these frogs are scattered in a small valley. The very restricted range of the new species of Cycloramphus and the declining quality of its habitat qualify this frog as critically endangered.
Keywords: Atlantic forest; conservation; Cycloramphus; insular herpetofauna; new species; southeastern Brazil